Accelerating small firms' production process improvement through international market knowledge and valuable, rare, inimitable, and organized resources and capabilities - M. Elfan Kaukab; Wiwiek Rabiatul Adawiyah; Refius Pradipta Setyanto; Agus Suroso (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
This article aims to explore the factors influencing MSMEs - Micro, Small, and Medium Enterprises production process improvement using variables of VRIO (Value Rarity, Inimitability, and Organization) resources and capabilities, foreign market knowledge, and internationalization. This research is conducted in 150 exporting-MSMEs samples in Central Java, Indonesia. The main analysis applied in this research is multiple regressions. The result shows that VRIO resources and capability, foreign market knowledge, and internationalization, significantly influenced production process improvement. It emphasizes that degree of internationalization only weakly influencing process improvement. The more important factors are internal factors like knowledge, resources, and capability. The result obtained can be used as the basis to develop the strategy of capability improvement for MSMEs in designing internationalization strategy. The strategy will closely relate to MSMEs' process improvement to compete in international market. This research provides two contributions. First, the internationalization of handicraft MSMEs does not strongly define MSMEs production process improvement. Second, process improvement can be accelerated by gaining market knowledge and exploiting valuable, rare, inimitable, and organized resources and capabilities.
Keywords: F23; L26; M31; 650; handicraft MSME; process improvement; foreign market knowledge; VRIO resources; and capability; MSMEs internationalization